ANALISIS PERBAIKAN FAKTOR DAYA MENGGUNAKAN KAPASITOR BANK DI PLANT 6 PT. INDOCEMENT TUNGGAL PRAKARSA Tbk. UNIT CITEUREUP - Ibnu Hajar; Suninda Megi Rahayuni (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
PT. Indocement Tunggal Prakarsa Tbk. is a company that produces cement. Large electrical power requirements are a major factor in running production process. The low power factor caused load system in Plant 6 not to run optimally. For industries, low power factor conditions could not be avoided due to varying motor loads. The power factor improvement used capacitor banks. The power factor is the ratio of active power with apparent power. Capacitor banks are a set of several capacitors connected in parallel to improve the quality of electrical power by increasing the power factor. This study used a quantitative method in which there was clarity of purpose, approach, data sample, and abundantly use of number. Moreover, data analysis was undertaken after all data had been collected. By raising the Cos  to 0.95, for the main feeder AA 5 (from main transformer 6.1), a capacitor of banks with a capacity of 6172.33 kVAR must be installed, and for main feeder AA 8 (from main transformer 6.2), a capacitor of banks with a capacity of 5388.88 kVAR must be installed in order that the quality power produced was more optimal.